2018
DOI: 10.1007/s10620-018-5417-5
|View full text |Cite
|
Sign up to set email alerts
|

Branched Short-Chain Fatty Acid Isovaleric Acid Causes Colonic Smooth Muscle Relaxation via cAMP/PKA Pathway

Abstract: Background.-Isovaleric Acid (IVA) is a 5-carbon branched chain fatty acid present in fermented foods and produced in the colon by bacterial fermentation of leucine. We previously reported that the shorter, straight chain fatty acids acetate, propionate and butyrate, differentially affect colonic motility; however, the effect of branched chain fatty acids on gut smooth muscle and motility is unknown. Aims.-To determine the effect of IVA on contractility of colonic smooth muscle. Methods.-Murine colonic segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 60 publications
0
21
0
2
Order By: Relevance
“…1 f and Figure S2 A and B). Since iso-valeric acid has been related to colon smooth muscle cell relaxation [ 24 ], we considered the study of this microbial metabolite in intestinal epithelium, through the different in vitro responses. Further in this line, motilin, an important protein associated with gastrointestinal motility, was also quantified (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 f and Figure S2 A and B). Since iso-valeric acid has been related to colon smooth muscle cell relaxation [ 24 ], we considered the study of this microbial metabolite in intestinal epithelium, through the different in vitro responses. Further in this line, motilin, an important protein associated with gastrointestinal motility, was also quantified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Depressive symptoms and depressive-like behavior are frequently perceived in both patients and experimental models of MS [ 39 , 40 ]. Moreover, iso-valeric acid has also been found to block motility of colon smooth muscle cells [ 24 ], therefore directly contributing to constipation, one of the clinical signs in EAE and MS. Since we found IL-8 upon stimulation of colon epithelial cells with iso-valeric acid, this SCFA could contribute to the inflammatory environment of EAE, deserving further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although straight‐chain SCFAs, primarily butyrate and propionate, have been shown to have a prokinetic effect by promoting contraction of smooth muscle in the colon in ex vivo studies evaluated in colonic tissue from dogs, cats, and guinea pigs, BCFAs and other products of protein fermentation in the colon are considered deleterious to the gut. For example, isovaleric acid has been shown to cause colonic smooth muscle relaxation in an ex vivo rodent model . In addition, decreased gastrointestinal motility has been linked directly to uremia by causing dysbiosis and colonic inflammation secondary to increased uremic toxin exposure in rodent models .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BCFAs represent only a small portion (5%) of total SCFA production and are produced when protein passes through the small intestine unabsorbed and protein‐derived branched chain amino acids are fermented by microbiota in the colon . Branched‐chain SCFAs and other products of protein fermentation in the colon are considered deleterious to the gut and may promote inflammation as well as have negative effects on motility in a rodent model …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Previous reports showed that BCFAs affect energy metabolism and cause colon smooth muscle relaxation. 18,19 Another report demonstrated that enterochromaffin cells are activated by a microbial metabolite, IVA, via Olfr558. 20 However, much remains unknown regarding whether BCFAs regulate additional cellular activities and differentiation.…”
Section: Introductionmentioning
confidence: 99%